The Role of Flow in the Everglades Landscape - Holly E. Fling; Nicholas G. Aumen; Tom Armentano; Frank J. Mazzotti (EDIS)
The Comprehensive Everglades Restoration Plan (CERP) aims to improve water quantity, timing, distribution, and quality of the Greater Everglades System (Figure 1) over the next 35 years (SFERTF 1998). Not only is it the most expensive (8 billion dollars, 1999) and ambitious ecological restoration ever undertaken, but it involves multiple agencies and organizations analyzing natural and ecological attributes to recover the natural system. A critically important but often overlooked aspect of the Everglades is the role of flow--the actual movement of water across the landscape--in creation and maintenance of habitats for Everglades plants and animals. Successful restoration of the Everglades landscape requires a thorough understanding of the role of flow (SCT 2003). This document is CIR1452, one of a series of the Wildlife Ecology and Conservation Department, University of Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences. Publication date: December, 2004.